PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN WORDWALL PADA PELAJARAN IPS KELAS IV DI UPT SDN 16 SUPAYANG - Desra Mega Pertiwi (Amal Insani Foundation, 2024)
ABSTRACT This study was conducted to find out how student learning outcomes can be improved by using wordwall learning media in social studies learning. This study used classroom action research. The subjects used were grade IV students.This research was carried out in two cycles consisting of planning, action, observation, and reflection. The data collection technique used is a test. This research was motivated by the many learning outcomes of students under the school KKTP, which is 75. Based on research conducted by students who completed only 3 people classically with an average of 24%.When given actions using wordwall learning media, there is an increase in learning outcomes. Students who completed were 7 people, a classical completion rate of 41% and an average of 68.8. Based on the results obtained from cycle I, researchers proceed to Cycle II by varying the use of wordwall media in the form of games. After the second cycle was carried out,student learning outcomes showed an increase, namely the classical completeness of students reached 76% with an average of 82.4. So it can be concluded that the use of wordwall learning media can improve the learning outcomes of social studies class students of UPT SDN 16 Supayang.